2023
DOI: 10.1002/pri.2047
|View full text |Cite
|
Sign up to set email alerts
|

The difference in multifidus muscle morphology and motor control in non‐specific low back pain with clinical lumbar instability and healthy subjects: A case‐control study

Eman Masry Abdelaty,
Salwa Shendy,
Osama Lotfy
et al.

Abstract: BackgroundLow back pain (LBP) with clinical lumbar instability (CLI) is considered a subgroup of back pain. Poor core stability function and/or lack of motor controls are thought to play a role in inappropriate inter‐segmental movements and pain. There is no study investigating the changes in the lumbar multifidus muscle (LMM) morphology and motor control in this subgroup of patients.ObjectiveTo assess motor control components and morphological changes of LMM in the patients suffering from chronic nonspecific … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 60 publications
1
0
0
Order By: Relevance
“…Several studies have investigated the relationship between lumbar muscle morphology and different types of LBP. Consistent with the results of the present study, the changes in motor control, increasing MF fat infiltration and decreasing MF thickness were reported by Abdelaty et al in patients with CNLBP with clinical lumbar instability [ 25 ]. Others such as Dayani et al [ 26 ] found smaller MF size in CNLBP patients and Gobert et al [ 27 ] found increased fat infiltration in the MF muscle with no change in total CSA in patients with CNLBP compared to patients with acute LBP.…”
Section: Discussionsupporting
confidence: 93%
“…Several studies have investigated the relationship between lumbar muscle morphology and different types of LBP. Consistent with the results of the present study, the changes in motor control, increasing MF fat infiltration and decreasing MF thickness were reported by Abdelaty et al in patients with CNLBP with clinical lumbar instability [ 25 ]. Others such as Dayani et al [ 26 ] found smaller MF size in CNLBP patients and Gobert et al [ 27 ] found increased fat infiltration in the MF muscle with no change in total CSA in patients with CNLBP compared to patients with acute LBP.…”
Section: Discussionsupporting
confidence: 93%